Analysis of Rice Production and Contributions to Cambodian Economic Growth - Voeurn Nhat (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study focuses on an analysis of rice production and contributions to Cambodian economic growth. There are three main objectives that are focused upon. First, it aims to analyze the situation of rice production in Cambodia using Diamond Model. Second, it investigates the factors that could impact on rice production and evaluates the rice export contributions to Cambodian economic growth. Third, it attempts to provide the best fitted ARIMA model that would be employed to make an accomplish forecast rice production in Cambodia. In the first objective, our study reveals that huge potential opportunities for Cambodian rice production expansion when comparing with neighboring countries (Thailand and Vietnam) and that Cambodian farmers can response to high prices and productivities by increasing their use of inputs such as seeds, fertilizers, irrigation, harvested area and machinery. In the second objective, this study uses ARDL model to analyze time series data over the period of 50 years (1961 - 2010) in order to examine the factors that affect rice production. We find that seeds, fertilizers, machinery, irrigation and harvested area have a positive effect on rice production in Cambodia. It also uses ARDL model to analyze time series data over the period of 15 years (1996 - 2011) to investigate the rice export contributions to Cambodian GDP growth. The results indicate that rice export has a significant and positive impact on Cambodian GDP growth. The third objective, the study also employs ARIMA model to analyze time series data over the period of (1960 - 2013) to examine the best ARIMA model that can be used to employ historical forecast rice production in Cambodia from 1960 to 2013. We find that the ARIMA (1, 1, 1) is the best fit model for forecasting rice production. This may suggest that Cambodian government should design a strategy that assists credit on machinery, irrigation, harvested area, seeds and fertilizers to farmers in order to increase rice production and promote economic growth by increasing rice export. Government also needs to pay close attention to make an investment strategy that stimulate rice production in Cambodia.